Case report: Intravascular large B cell lymphoma mimicking acute demyelinating encephalomyelitis after SARS-CoV-2 reinfection: diagnostic value of advanced MRI techniques and the literature review with the assistance of ChatGPT - Chen, Sujuan; Cai, Mingchen; Tan, Guirong; Guo, Ruomi; Liang, Qiong; Li, Hainan; Liu, Xiang (Frontiers in Immunology, 2024)
The intravascular large B cell lymphoma (IVLBCL) is a rare subtype of lymphoma. The IVBCL is usually found with systemic involvement, with a relative predilection for skin and the central nervous system (CNS), followed by a rapidly progressive course and poor prognosis with a high mortality rate. IVLBCL is difficult to diagnose based on conventional MRI alone. Herein, we presented a previously healthy 59-year-old woman who developed hemiparesis and altered mental status after her reinfection of SARS-CoV-2. The initial MRI revealed non-enhancing lesions in the splenium of the corpus callosum (CC), periventricular, and bilateral subcortical white matter with hyperintensity on diffusion weighted imaging (DWI). The patient was diagnosed with subacute infarction and she was treated with antithrombotic therapy. Her neurological symptoms continued to deteriorate and she developed unconsciousness. Her CSF test showed elevated white cell count and positive oligoclonal bands. The follow-up MRI was scanned 16 days later. Compared to the initial MRI, the periventricular and bilateral subcortical lesions enlarged on conventional MRI. The post-contrast 3D black blood Cube images demonstrated multiple parenchymal and diffuse meningeal enhancements and 3D arterial spin labeling showed increased perfusion in the CC splenium. These findings suggested the differential diagnosis of acute demyelinating encephalomyelitis (ADEM) after SARS-CoV-2 reinfection, versus intravascular lymphoma. After the treatment of intravenous immunoglobulin and methylprednisolone, her symptoms significantly improved. The second follow-up MRI two weeks later detected a new unenhanced lesion in the left temporal lobe. A brain biopsy was performed and IVLBCL was diagnosed. We reviewed the brain MRI findings of IVLBCL in the literature with the assistance of ChatGPT. Although less specific, the imaging features including “high signal lesions on DWI, meningeal thickening and enhancement, and masslike lesions” highly suggested the possibility of IVLBCL. The biopsy should be planned after imaging progression. The association between IVLBCL and SARS-CoV-2 reinfection is undefined.